The TanDEM-X Mission Concept - Zink, Manfred; Krieger, Gerhard; Fiedler, Hauke (2007)
TanDEM-X (TerraSAR-X add-on for Digital Elevation Measurement) opens a new era in space borne radar remote sensing. A single-pass SAR-interferometer with adjustable baselines in across- and in along-track directions is formed by adding a second (TDX), almost identical spacecraft, to TerraSAR-X (TSX) and flying the two satellites in a closely controlled formation. TDX has SAR system parameters which are fully compatible with TSX, allowing not only independent operation from TSX in a mono-static mode, but also synchronized operation (e.g. in a bi-static mode). With typical across-track baselines of 200-400m DEMs according to the High Resolution Terrain Information (HRTI)-3 standard will be generated. The HELIX concept provides a save solution for the close formation flight with vertical separation of the two satellites over the poles and adjustable horizontal baselines at the ascending/descending node crossings. DEMs are of fundamental importance for a broad range of scientific and commercial applications. For example, many geoscience areas like hydrology, glaciology, forestry, geology, oceanography and land environment require precise and up-to-date information about the Earth’s surface and its topography. Digital maps are also a prerequisite for reliable navigation, and improvements in their precision needs to keep step with the advances in global positioning systems. Beyond the generation of a global HRTI-3 DEM as the primary mission goal, local DEMs of even higher accuracy level (HRTI-4) and applications based on Along-Track Interferometry (ATI) like measurements of ocean currents, sea ice drift and glacier flow are important secondary mission objectives. Along-track interferometry will also allow for innovative applications to be explored and can be performed by the so-called dual-receive antenna mode on each of the two satellites and/or by adjusting the along-track distance between TSX and TDX to the desired value. Combining both modes will provide a highly capable along-track interferometer with four phase ...